GDF-8 improves in vitro implantation and cryo-tolerance by stimulating the ALK5-SMAD2/3 signaling in bovine IVF embryo development - Seon-Min Kang; Muhammad Idrees; Muhammad Idrees; Chalani Dilshani Perera; Seo-Hyun Lee; Mingjun Zhang; Xianfeng Yu; Yongxun Jin; Il-Keun Kong; Il-Keun Kong (Frontiers in Cell and Developmental Biology, 2024)
Transforming growth factor-beta (TGF-β) plays a critical role in regulating trophoblast invasion and proliferation. Growth differentiation factor-8 (GDF-8) is a member of the TGF-β superfamily and is categorized as a myostatin subtype. It is primarily a secreted protein synthesized in skeletal muscle cells. It is expressed in the placenta, reproductive tissues, and cells. In this study, we investigated the role of GDF-8 in the development and hatching rate of bovine embryos. We noted a notable elevation (p < 0.05) in the development and hatching rates compared to the control embryos. Furthermore, the GDF-8 group showed a significantly improved total cell number (p < 0.05) and an increase in trophectoderm ratio inner cell mass (trophectoderm: inner cell mass) cells (p < 0.001) compared to the control group. Additionally, blastocysts treated with GDF-8 exhibited significantly higher mRNA levels of caudal-type homeobox 2 (CDX2) (p < 0.05). The trophoblast invasion area was significantly larger in the GDF-8 group than in the control group (p < 0.01). Furthermore, qRT-PCR analysis revealed significantly higher mRNA levels (p < 0.05) of matrix metalloproteinases 9 (MMP9) and follistatin-like 3(FSTL3), both of which are associated with the ALK5-SMAD2/3 signaling pathway, in the GDF-8 group than those in the control group. The mRNA expression levels of genes related to tight junctions (TJ) and adherent junctions were higher in the GDF-8 group than those in the control group (p < 0.05). After 24 h of thawing, blastocysts were analyzed using 4-kDa FITC-dextran, which revealed a higher TJ integrity in the GDF-8 group (p < 0.01). Thus, GDF-8 plays a crucial role in bovine embryonic development, in vitro implantation, and cryotolerance.